Factors Associated with the Irregularity of Antenatal Care Visits at the Amandraya Health Center in South Nias Regency in 2022 - Hondro, Surya Meistin Kristianti; Pasaribu, Veronika Sinar Open; Purba, Edy Marjuang; Manurung, Herna Rinayanti; Dewi, Eva Ratna; Marliani, Marliani (Sean Institute, 2022)
Antenatal care is an activity of supervising pregnant women to prepare pregnant women as well as possible both physically and mentally, as well as saving mothers and babies during pregnancy, childbirth and the postpartum period. In South Nias District the coverage of Antenatal Visits 1 (K1) was 87.10% in 2019 and K4 was 73.32. At the Amandraya Health Center the coverage of K1 to K4 in 2021 has not reached the expected target of 95%. The aim of this study was to find out the factors associated with the irregularity of antenatal care visits at the Amandraya Health Center in South Nias Regency in 2022. This type of research is an analytic observational study using a cross sectional approach. The population was all pregnant women at the Amandraya Health Center in South Nias Regency, namely 217 people. The sample in this study were 73 people obtained through simple random sampling technique. Data analysis was carried out to determine the distribution of frequencies and percentages of each variable to be studied which included: age, education, employment, parity, income and staff support. Data analysis was performed by statistical test using chi-square. There is a relationship between knowledge (p=0.001) and income (p=0.007), mothers and irregular antenatal care visits at the Amandraya Health Center in South Nias Regency in 2022. There is no relationship between mother's education, number of children and health workers and irregular antenatal care visits. It is suggested to the staff of the Amandraya Health Center in South Nias Regency to increase counseling activities so that pregnant women's knowledge about antenatal care increases and antenatal care visits can be carried out regularly from the 1st to the 3rd trimester.